SERTIFIKASI TANAH SEBAGAI INSTRUMEN PERLINDUNGAN HUKUM DAN JAMINAN INVESTASI UNTUK MENDUKUNG KEGIATAN EKONOMI PENGGUNAAN ASET TANAH - Antonius Ade Yunus Sihaloho (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
Land is a strategic asset that has multidimensional functions, including social, cultural, legal, and economic functions. However, in practice, land often becomes the subject of disputes due to the lack of certainty regarding ownership status. Land certification serves as a legal protection instrument and a guarantee for investments with high strategic value. This study qualitatively examines two main aspects through a literature review: first, how land certification functions as a legal protection instrument for ownership rights; and second, how land certification acts as an investment guarantee in supporting economic activities involving the use of land assets. The results of the study show that land certificates have legal force that provides certainty, prevents conflict, and serves as valid evidence in court, thereby guaranteeing protection for the owner. On the other hand, land certificates also provide economic benefits through increased asset value, strengthened trust in the financial system, and access to business capital by making them valid collateral in banking. Thus, land certification is not only an administrative instrument but also the foundation for economic development based on legal certainty and sustainable investment.